ANALGESIC ACTIVITY OF SOME NEW DECAHYDROQUINOLINE DERIVATIVES. - Goncharukl, V V; Buben, A L; Borisenok, O A; Kozlovskii, V I; Pun'ko, I M; Vdovichenko, V P; Praliev, K D (Ėksperimentalʹnaâ i kliničeskaâ farmacologiâ, 2016)
The work was aimed at assessing in vivo the analgesic properties of ten decahydroquinoline derivatives (pharmacologically active substances, PAS) and deter- mining the role of opioid receptors in mechanism of their action. Among the derivatives studied, pronounced analgesic properties at a dose of 1/4 LD50 was ob- served for two compounds (PAS-70 and PAS-71), while four compounds (PAS-66, PAS-69, PAS-74, PAS-76) produced weak and short anesthetic effects. PAS-70 and PAS-71 showed analgesic action even in a dose of 1/8 LD50. The maximum effect of PAS-70 and PAS-71 was developed within 20 - 60 min after administration and lasted for two hours (PAS-70 in a dose of 1/4 LD50, PAS-71 in doses of 1/4 and 1/8 LD50). The analgesic effect of PAS-70 (at 1/4 LD5,) and PAS-71 (at 1/4 and 1/8 LD50) significantly exceeds that of reference drugs metamizol (1/4 LD5) and ketorolac (1/4 LD50). The mechanism of drug action is not related to opioid receptors.